Organic Trace Minerals at Lower Concentrations Can Replace Inorganic TraceMineral Premix in Broiler Chicken Diet - Rama Rao, S. V.; Raju, M. V. L. N.; Nagalakshmi, D.; Savaram, Anusha; Pavan, S. Sai; Prakash, B.; Srilatha, T.; Paul, S. S.; Kannan, A. (Indian Journal of Animal Nutrition, 2025)
An experiment was conducted to study the performance, immune responses, and bone mineral variables in broiler chickens fed organic trace minerals (oTM) at suboptimal concentrations in the diet. A total of 2080 day-old broiler male chicks were randomly distributed into floor pens (6.25 × 4 feet) at the rate of 26 birds per pen. Maize-soybean meal-based control diet was supplemented with inorganic trace mineral premix (iTM; Fe 100, Zn 100, Mn 100, Cu 20, Se 0.50, I 2.5/mg/kg). The iTM premix was replaced in the test diets with oTM to provide minerals at graded levels in the diet (10, 17.5, and 25% of the control diet). Each diet was fed ad libitum to a total of 20 replicates of chicks from 1 to 42 days of age. The body weight gain (BWG) was not affected by supplementing oTM at 20% during 1-14 and 1-28 d of age. Both BWG and feed conversion ratio (FCR) were significantly reduced with an increase in oTM >35%. Both the production variables in groups fed oTM at 20% were similar to those fed the iTM. The relative weight of breast meat was lower (p<0.05) and liver weight was higher (p<0.05) in groups fed the higher concentration of oTM (50%) than the iTM group. Similarly, tibia breaking strength and P content in tibia ash in oTM 20% were similar to broilers fed on iTM. Tibia ash and Ca content in tibia ash were not affected by dietary variation in the mineral source (iTM vs oTM) and organic mineral concentration. Based on the results, it is concluded that trace mineral supplementation can be reduced to 20% when fed in organic form in broiler chicken diet to support the optimum growth, mineralization, and HI titer to ND vaccine.